ANALISIS PELAYANAN PUBLIK DI KANTOR KEUCHIK DESA GUNONG KLENG KECAMATAN MEUREUBO KABUPATEN ACEH BARAT - Vera Septia Phurma; Najamudin Najamudin Najamudin (Faculty of Social Science, Universitas Negeri Padang, 2022)
Public service is a series of fulfillment of needs based on applicable service procedures. The quality of service greatly determines the satisfaction of service recipients, the better the service provided, the higher the quality of service. Service quality can be measured through the principles of public service, namely, transparency, accountability, conditional, participatory, equal rights, balance of rights and obligations. The purpose of this study is to analyze the public services run by the Gunong Kleng Village Government through a comparison with the principles of Law Number 25 Year 2009 concerning the quality of government public services. The type of research method used is qualitative through a descriptive analysis approach in order to obtain a description of the public services carried out in Gunong Kleng Village in accordance with the established principles of public service. Data collection techniques used are observation, interview and documentation techniques. The results of the public service analysis show that the Gunong Kleng Village Government, West Aceh Regency has carried out public services well and complied with the aspects of Law Number 25 of 2009.